METHOD DEVELOPMENT AND VALIDATION OF EPROSARTAN MESYLATE AND ITS IMPURITIES USING REVERSE PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY - Chandana, O. S. S.; Kumar, D. Sathis; Babu, R. Ravichandra (International Journal of Current Pharmaceutical Research, 2016)
Objective: Our main objective is to develop an accurate and precise RP-HPLC method for the determination of Eprosartan Mesylate and its impurities. Methods: A Develosil ODS UG-5; (150 × 4.6) mm; 5 µm column was used for the Separation of drugs by a mobile phase consisting of Buffer and Acetonitrile mixture in the gradient proportion. The flow rate maintained was 0.8 ml/min and the wavelength used for detection was 235 nm. Results: The linearity was observed in the range of 0.025-50µg/ml of spiked impurities in Eprosartan Mesylate, impurity 1 and impurity 2 with a correlation coefficient of 0.99927, 0.99910 and 0.99934 respectively. The mean percentage recoveries for LOQ, 50%, 80%, 100%, 150% and 200% accuracy were found to be 101.5±1.51, 107.0±1.7, 104.6±0.4, 102.8±0.36, 101.7±0.26 and 101.3±0.15 respectively for impurities in Eprosartan Mesylate, impurity 1 and impurity 2. Linearity, accuracy, precision and robustness parameters for the suggested method were estimated for validation. Conclusion: The developed method is uncomplicated, accurate, sensitive and precise for the determination of related substances in the Eprosartan Mesylate. The satisfying % recoveries and low % RSD Values confirmed the suitability of the developed method for the usual analysis of Eprosartan mesylate in pharmaceuticals.